Delegation and Overhead Aversion with Multiple Threshold Public Goods - Diya Elizabeth Abraham; Luca Corazzini; Miloš Fišar; Tommaso Reggiani (Masaryk University, Faculty of Economics and Administration, 2021)
Experimental studies have modeled individual funding of social projects as contributions to a threshold public good. We examine donors' behavior when they face multiple threshold public goods and the possibility of coordinating their contributions via an intermediary. Employing the experimental design developed in Corazzini, Cotton, and Reggiani (2020), we vary both the size of a `destination rule', which places restrictions on the intermediary's use of a donor's funds, as well as the overhead cost of the intermediary, modeled as a sunk cost incurred by the intermediary whether or not any of the public goods are successfully funded. We show that subjects behave in line with equilibrium predictions with regard to the size of the destination rule, only increasing their contributions in the presence of a relatively high destination rule that prevents expropriation by the intermediary. However, we find that the positive effect of a high destination rule is undone in the presence of overhead sunk costs on the intermediary, thus providing evidence in favor of the sunk-cost bias and `overhead aversion' that are commonly exhibited by donors when selecting charities.
Keywords: C91; C92; H40; H41; L31; 330; overhead aversion; threshold public goods; delegation; fundraising